The Effect of Dividend per Share and Earnings per Share on Stock Prices of Consumer Non-Cyclicals Sector Companies - Ni Gusti Ayu Marcella Zerlyanti; I Made Pande Dwiana Putra (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Supply, demand, and the decisions made by capital market participants all affect a stock’s price, which is its present worth on the stock exchange. Consistent increases in stock prices reflect the success of management in managing the business and attracting investor interest. This study aims to investigate the relationship between dividends and earnings per share and stock prices. Companies in the non-cyclical consumer sector that were listed on the Indonesia Stock Exchange between 2021 and 2023 make up the study’s population. The sample consists of 155 observations selected using purposive sampling techniques. Through non-participant observation, data were gathered. Multiple linear regression analysis is the method of analysis that is employed. The results of the study indicate that stock values benefit from dividends and earnings per share. Because they show the financial performance of the business and dividend-paying capacity, both earnings and dividends per share are seen by investors as positive signals when making investment decisions. This finding is consistent with the signal theory. Companies are advised to implement a consistent dividend per share distribution policy and increase profitability in order to strengthen investor confidence.